(untitled) (Bangladesh Journal of Child Health, 2021)
Background: Mechanically ventilated neonates are usually exposed to high oxygen therapy and due to common clinical practice and lack of knowledge about the target and optimum dose & duration of oxygen administration hyperoxia occurs frequently. The study was done to compare the effect between conventional high flow and conservative oxygen therapy. Materials & Methods: A prospective study was done in Dhaka Shishu Hospital NICU from July 2013 to June 2014 and enrolled those were underwent invasive mechanical ventilation. Ventilator settings, FiO2 and SpO2 were recorded for the first 48 hours. The comparison of conventional high FiO2 (> 0.7-1.0) and conservative FiO2(< 0.7) therapy was assessed by SpO2, PaO2, PaO2/ FiO2 ratio and lung injury score within 48 hours of exposure and was analyzed. Results: Among total 40 cases 30/40(75%) were exposed to conventional high FiO2. After invasive mechanical ventilation, there was improvement of SpO2 in both group (76.7% vs 70%) but there was no significant difference in between conventional high FiO2 implementation and conservative group(P=0.67). PaO2/ FiO2 ratio also improved after ventilation (145.17 vs 328.40, P=0.013) in both groups but indicate lung injury in conventional high FiO2 group. After invasive mechanical ventilation 53% (16/30) patients were suffering from acute lung injury(ALI) & acute respiratory distress syndrome (ARDS) with high exposure of FiO2 (>0.7-1) and only 40% (4/10) patient developed ALI & ARDS in low exposure group (FiO2<0.7). Conclusions: Conventional high FiO2 or liberal O2 therapy in mechanically ventilated neonates improves SpO2 but conventional high FiO2 may causes iatrogenic lung injury. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 19-24